2013
DOI: 10.1371/journal.pone.0059193
|View full text |Cite
|
Sign up to set email alerts
|

A Rat Model for Muscle Regeneration in the Soft Palate

Abstract: BackgroundChildren with a cleft in the soft palate have difficulties with speech, swallowing, and sucking. Despite successful surgical repositioning of the muscles, optimal function is often not achieved. Scar formation and defective regeneration may hamper the functional recovery of the muscles after cleft palate repair. Therefore, the aim of this study is to investigate the anatomy and histology of the soft palate in rats, and to establish an in vivo model for muscle regeneration after surgical injury.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…The aim of this study was to evaluate the regeneration of myofibers and the development of fibrotic tissue after injury. We previously demonstrated that the anatomy and histology of the soft palate muscles of the rat are largely comparable to that of humans . Here, we show for the first time that muscle regeneration in the soft palate of the rat after excisional injury is incomplete.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The aim of this study was to evaluate the regeneration of myofibers and the development of fibrotic tissue after injury. We previously demonstrated that the anatomy and histology of the soft palate muscles of the rat are largely comparable to that of humans . Here, we show for the first time that muscle regeneration in the soft palate of the rat after excisional injury is incomplete.…”
Section: Discussionmentioning
confidence: 51%
“…As previously described, the animals received buprenorphine (0.02 mg/kg s.c.; Temgesic, Schering Plough, Brussels, Belgium) as an analgesic before surgery and at 12‐hour intervals for the next 2 days. Briefly, animals in groups 2–5 were anesthetized and placed on an operating table in a supine position for surgery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle repair following injury is facilitated by SCs. Satellite cells are muscle stem cells originating from the CPM that are responsible for postnatal muscle growth, maintenance, and repair . They express the paired box transcription factor 7 (Pax7) and are located between the sarcolemma and basal lamina surrounding a single muscle fiber.…”
Section: Stem Cells Repair Wounds and Facilitate Skin And Muscle Regementioning
confidence: 99%
“…They express the paired box transcription factor 7 (Pax7) and are located between the sarcolemma and basal lamina surrounding a single muscle fiber. After the injury, SCs become activated and migrate to the site of injury, proliferate, and differentiate into myoD‐positive myoblasts that fuse to form new multinucleated myosin heavy chain (MyHC)‐positive myofibers or repair damaged myofibers (Figure ) . A small portion of these SCs stay quiescent to allow future regeneration cycles.…”
Section: Stem Cells Repair Wounds and Facilitate Skin And Muscle Regementioning
confidence: 99%